PENGGUNAAN BEBERAPA HORMON ORGANIK SEBAGAI MEDIA TUMBUH UNTUK MENINGKATKAN PERTUMBUHAN AZOLLA MICROPHYLLA SEBAGAI PAKAN TERNAK - Hia, Aro Setiawan; Meriksa Sembiring; Risdawati Br Ginting; Andhika Putra (Journal of Innovation Research and Knowledge, 2023)
This study aims to get the best organic hormone that can increase the growth and production of Azolla microphylla for animal feed. As well as knowing the best hormones from several plants as a growing medium for Azolla microphylla. The ingredients used in this study were hormones or ZPT from banana weevils, bean sprouts and yam leaves. The experimental design used in this study was a non-factorial Complete Randomized Design (RAL), consisting of 4 treatments with 5 repeats as a block until 20 experimental units were obtained. Each experimental unit has 3 replicates of sample plants, so that there are a total of 60 sample plants. The four treatments consist of: Z0 (control) without hormones, Z1 (hormones from banana weevils), Z2 (hormones from bean sprouts), Z3 (hormones from sweet potato leaves). The data were analyzed using variety analysis (anova) with 95% significance, if there is a real difference followed by further Duncan Multiple Range Test (DMRT). Based on this study, the use of hormones from bean sprouts (green bean sprouts) as ZPT is the best organic hormone as a natural growth regulator because it can increase growth, colony diameter and production of Azolla microphylla. The use of organic hormones from bean sprouts was able to increase the number of populations (stems) with an average of 94.95 sticks 7 hst, 345.24 sticks 14 hst, 426.81 sticks 21 hst, and 571.89 bars 28 hst. With an average colony diameter of 29.78 cm 7 hst, 66.27 cm 14 hst, 94.78 cm 21 hst and 166 cm 28 hst. And with an average production of 22.29 g 7 hst, 49.25 g 14 hst, 70.17 g 21 hst, 90.26 g 28 hst